Considerations for Measurement of Sodium Intake. Issue 6 (November 2020) - Almeida, Vanessa; Seto, Todd; Banna, Jinan
Current salt consumption is the major risk factor for hypertension and consequently cardiovascular disease (CVD). Accurate measurement of Na intake is an important component of developing dietary interventions to treat hypertension and lower CVD risk. Given that existing methods have a large subject burden, quick and practical ways to assess Na intake in individuals, particularly in hypertensive subjects, are needed. Such tools may be used for motivation to quantify salt intake and to set targets for lifestyle changes for prevention of CVD within a clinic setting. Patients at high risk of development of CVD may be identified and targeted for motivational interviewing. They may also be used as part of cardiac rehabilitation programs and will allow individuals to measure their own intake and to see the results of their individual action.